Communication experiences of Female Legislator DPRD Central Java Province Period of 2014/2019 in Committee Meeting - Mia Michaela; Agus Naryoso, S.Sos, M.Si (Interaksi Online, 2016)
Legislators have the role as puclic speakers representing the public in the government. Being the minors in the legislature, female legislators’ public speaking ability would be severely tested if they want to make sure their voices are heard during the decisions making. This research used a qualitative approach and constructivism paradigm which is aimed to describe how the communication experiences of female legislator DPRD Provinsi Jawa Tengah period of 2014/2019 in committee meeting. The theories used consist of: Aristoteles Rhetoric Theory and Gender Communication Theory. Unit analysis of this research was three female legislators of DPRD Provinsi Jawa Tengah. The result of this research are that the difference of public speaking style wasn’t only found in the context of male and female legislators of DPRD Provinsi Jawa Tengah only, but even the female legislators have different style of public speaking. Moreover the stereotype about female communication style wasn’t found anymore on female legislator of DPRD Provinsi Jawa Tengah, but the culture of Central Java which is rich of courteousy, manners and rather not using high intonacy and tones, and also the formal procedures and informal etiquettes influence the public speaking style of all of the legislators, not only the females. Both the male and female legislators are positioned on the same position during the comitte meetings, without discriminations. But, the stereotype about women itself and the lack of recognition of their ability indeed put the female legislators in unstrategic position, such as the lack of female leaders on the leadership structures inside the legislature. This research concludes that female legislators of DPRD Provinsi Jawa Tengah still have some troubles to do their role as a public speaker in the legislature from the stereotype and the Central Java cultures about females, that demand politeness and softness in their behaviours and also yet to recognize female’s abilities as leaders.